Electromobility in Poland Compared to the European Union – Results of Preliminary Analysis - Bełch, Paulina; Szczygieł, Elżbieta; Hajduk-Stelmachowicz, Marzena (Elektromobilność w Polsce i Unii Europejskiej – wyniki wstępnej analizy porównawczej, 2024)
The article analyses the trends in the growth of electric vehicles (EVs) in Poland compared to the EU. Verification of the assumed objective required the application of research methods such as analysis of domestic and foreign literature, analysis of statistical data, and statistical inference. This article commences a series of publications on sustainable transport management and electromobility in Poland and selected European countries. The number of electric vehicles (BEV and PHEV) is still increasing in Europe, including Poland. In 2010, there were 591 registered EVs only which was only 0.005% of the whole number of cars registered in Europe. For the first time, the share of EVs exceeded 1% in 2015 (130,900 electric vehicles), and in 2020 more than 10% of EVs were in Europe (in 2021, 17.8%). The largest share of EVs in the total number of cars was recorded in 2021 in Norway (86%), in Iceland (64%), and in Sweden (46%). At the same time, the countries with the highest number of EVs include Germany (more than 2.5 million), France (1.7 m.), and Italy (1.4 m.).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 1, s. 1-13
Keywords: electromobility; Poland; European Union; analysis; transport; sustainable transport management; elektromobilność; Polska; Unia Europejska; zarządzanie zrównoważonym transportem